Genetic Diversity Analysis In Kabuli Chickpea (Cicer Arietinum L.) Genotypes Based On Quantitative Traits And Molecular Markers (Bangladesh Journal of Botany, 2022)
Chickpea (Cicer arietinum L.) provides high quality protein for human and animal consumption as well as offers economic benefits to farmers because of the high market value for its grains. Fifty indigenous and exotic kabuli chickpea lines varying in seed yield and plant type were subjected to 20 SSR markers analysis for assessment of genetic diversity. Among twenty SSR primers, eleven of them were able to produce polymorphic bands. Quantitative traits based clustering pattern was found to be similar to molecular clustering for most of the kabuli genotypes such as JGK 1, JGK 2, JGK 3, JGK 32-1 and some of the ICRISAT (ICCVs) and ICARDA (FLIPs) lines. This indicated the association of used molecular markers with targeted quantitative traits in the present study.Bangladesh J. Bot. 51(3): 581-587, 2022 (September)